Radio broadcasting, web radio and podcast: teaching audio journalism - Magnoni, Antonio Francisco [UNESP]; Almeida, William Douglas de; Leite, Wellington (Centro Univ La Salle-rj, 2020)
During the period of social isolation, carried out due to the coronavirus pandemic, the audience of radio stations in Brazil increased. Once again, the means of communication-based on simplicity and low cost showed efficiency as a source of services, information, and entertainment. This article discusses the evolution of radio over a century. From the centerpiece in the homerooms, through mobility and instantaneous, to the arrival of communication in podcasts. To prepare radio professionals, communication schools need to be attentive to technological changes and provide students with theoretical and practical knowledge about the production of audio content. As a methodology, a bibliographic review on the topic was made, in addition to the description of the case study on teaching radio journalism at a Communication Faculty. As main results, we highlight that the radio maintains a vast relevance as a low-cost medium and an extensive audience, being that at this moment the new technologies allow the exploration of new formats. It is also noteworthy that radio is no longer a communication vehicle of regional scope - currently, radio production has a global reach, likewise, it is marked by elements such as interactivity, multilateralism, portability, mobility, and individualized access and consumption.
Keywords: Radio; Communication; Journalism; New Technologies; Podcast